DETERMINANTS OF PARENTAL SCHOOL CHOICE: A SYSTEMATIC REVIEW OF THE LITERATURE - Bekele, Mekete Shiferaw; Kenea, Ambissa (Sanata Dharma University Yogyakarta, 2024)
The study examined determinants of parental school choice internationally aiming to identify research gaps and providing suggestions for researchers. Articles published between 2000 and 2023 were searched from 9 databases and a total of 30 articles were included in the review. The result showed that parental school choice is critically affected by parent-related factors like parents’ education, income, family size, and education level of the children, and the school-related factors: quality of education, performance of teachers, school facilities, school cost, parent-teacher relationship, and school curriculums are the major ones. The safety/security related and children’s educational achievement is found slightly affecting factor on parental school choice. The research design of reviewed articles is found descriptive research although the explanatory research design was appropriate as it supports better. The study also identified factors for developing and developed countries are different. For developing countries socio-economy, income, family education, cost, curriculum, technology, proximity to home, number of children, and age of the child are the major ones. For developed countries: school quality, teacher performance, special programs, playground, training teachers, library service, student moral development, school performance, environment, school ranking, interaction with parents, discipline, curriculum structure, knowledge, result, and communication skills are paid attention for parental school choice decisions.